FACTORS ASSOCIATED WITH PERCEIVED HEALTH AMONG CAREGIVER WHO ARE TAKING CARE OF ELDERLY WITH SCHIZOPHRENIA - roudlotul jannah; Joni Haryanto; Yanis Kartini; Ah Yusuf (Alta Dharma Publisher, 2019)
A family caregiver is the most important person who cares for the elderly with schizophrenia. The elderly with schizophrenia had complete problems related to the aging process and also sign and symptoms of schizophrenia. Burden perceived the stress feel of a caregiver who is taking care of elderly schizophrenia influences of caregivers’ perceived health. The study aimed to examine factors associated with perceived health among caregivers who are taking care for elderly with schizophrenia. The cross-sectional study design was applied in this study. Eighty-eight samples were recruited using systematic random sampling. Data were analyzed by using correlation and chi-square with a significance level of p<0.05. The results showed that age, education level, income, level of self efficacy, and level of knowedge. Healthcare providers need to consider those factors to improve health outcomes and before deigning the intervention. In order to improve knowledge and self-efficacy of caregiver, peer support, and health promotion about caring elderly schizophrenia should be emphasized. Keywords: perceived health, caregiver, schizophrenia, elderly